Tonga : 2002 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Tonga. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that the economic activity in Tonga rebounded modestly in 2001/02, as real GDP growth accelerated from about 1\2 percent in 2000/01 (fiscal year July-June) to 1 1\2 percent in 2001/02. Conditions in agriculture improved owing to record-high prices for squash and vanilla. Construction rebounded sharply with the assistance provided by the international community to rebuild structures destroyed by Cyclone Waka. Tourism and the service sector have been sluggish during most of the past two years.